Electron Beams at Europa - F. Allegrini; J. Saur; J. R. Szalay; R. W. Ebert; W. S. Kurth; S. Cervantes; H. T. Smith; F. Bagenal; S. J. Bolton; G. Clark; J. E. P. Connerney; P. Louarn; et al. (Geophysical Research Letters)
Abstract Jupiter's moon Europa contains a subsurface ocean whose presence is inferred from magnetic field measurements, the interpretation of which depends on knowledge of Europa's local plasma environment. A recent Juno spacecraft flyby returned new observations of plasma electrons with unprecedented resolution. Specifically, powerful magnetic field‐aligned electron beams were discovered near Europa. These beams, with energies from ∼30 to ∼300 eV, locally enhance electron‐impact‐excited emissions and ionization in Europa's atmosphere by more than a factor three over the local space environment, and are associated with large jumps of the magnetic fields. The beams therefore play an essential role in shaping Europa's plasma and magnetic field environment and thus need to be accounted for electromagnetic sounding of Europa's ocean and plume detection by future missions such as JUICE and Europa Clipper.